2018
DOI: 10.1111/nph.14998
|View full text |Cite
|
Sign up to set email alerts
|

Ecological causes and consequences of flower color polymorphism in a self‐pollinating plant (Boechera stricta)

Abstract: Intraspecific variation in flower color is often attributed to pollinator-mediated selection, yet this mechanism cannot explain flower color polymorphisms in self-pollinating species. Indirect selection mediated via biotic and abiotic stresses could maintain flower color variation in these systems. The selfing forb, Boechera stricta, typically displays white flowers, but some individuals produce purple flowers. We quantified environmental correlates of flower color in natural populations. To disentangle plasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 74 publications
(122 reference statements)
2
48
0
1
Order By: Relevance
“…Color polymorphism may be a consequence of pollination competition or specific adaptations to pollinators, and pollinator behavior exerts strong selection stress on color variations. Some research also showed adaptive selection for pigmented flowers because colored flowers are less likely to be disrupted by herbivories than colorless ones [3]. According to our field observations, we found that white-flowered individuals were more susceptible to damage than individuals with pigmented flowers, and that white flower petals and cores were severely foraged when blooming.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Color polymorphism may be a consequence of pollination competition or specific adaptations to pollinators, and pollinator behavior exerts strong selection stress on color variations. Some research also showed adaptive selection for pigmented flowers because colored flowers are less likely to be disrupted by herbivories than colorless ones [3]. According to our field observations, we found that white-flowered individuals were more susceptible to damage than individuals with pigmented flowers, and that white flower petals and cores were severely foraged when blooming.…”
Section: Discussionsupporting
confidence: 54%
“…Flower color is one of the most attractive characteristics of plants in nature. With such massive variation, flower color is regarded as an evolutionarily labile trait and has been shown to contribute to plant evolution [1][2][3]. In particular, flower color adaptive mutations mediated through pollinators are directly relevant to phenotypic evolution [4].…”
Section: Introductionmentioning
confidence: 99%
“…We chose average summer climatic values because they are representative of the conditions experienced by flowers (see . In particular, temperature and drought are two factors shown to impose selection on anthocyanin-based petal coloration (e.g., Warren and Mackenzie, 2001;Lacey and Herr, 2005;Vaidya et al, 2018).…”
Section: Predictors Of Color Variation: Climatic Data Pollinator Datmentioning
confidence: 99%
“…Darker coloration can also be favored in drought conditions (Warren and Mackenzie, 2001). For example, in Boechera stricta, there is a greater likelihood of pigmented flowers in low elevation populations which may be due to elevated drought tolerance of pigmented morphs (Vaidya et al, 2018). Models that incorporate the effects of both abiotic and pollinator attributes of the environment on coloration can help to parse the impacts of each on floral color.…”
Section: Introductionmentioning
confidence: 99%
“…生 物 多 样 性 Biodiversity Science 第 27 卷 研究报告 同一种植物的不同个体也会表现出花色多态 性 (Stanton et al, 1986;Schoonhoven et al, 2007;Majetic et al, 2009;Koski & Ashman, 2016), 可能具 有不一样的适应意义 (Vaidya et al, 2018) 多态性 (Chang & Rausher, 1999); 萝卜(Raphanus sativus)通过两种花色分别提高雌雄功能 (Stanton et al, 1986), 也减少了植食动物的采食 (Irwin, 2003)。 同种植物的不同花色在种群内的分布频率有 时极不均衡。如根爪兰(Dactylorhiza sambucina)除 了常见的黄花和紫花个体, 还有分布频率极低(约 占 种 群 大 小 的 10%-20%) 的 粉 花 个 体 (Gigord, 2001)。 这些极低频率的粉花个体可能通过增加花色 多态性, 提高和延长了无报酬的根爪兰对传粉者的 吸 引 力 (Gigord, 2001) 。 十 字 花 科 自 花 授 粉 的 Boechera stricta白花个体易受植食动物取食 (Vaidya et al, 2018)…”
unclassified